Multibeam bathymetry processed data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM68 - Stefanie Gaide; Christian dos Santos Ferreira; Paul Wintersteller (PANGAEA, 2025)
Swath sonar bathymetry data used for that dataset was recorded during RV MARIA S. MERIAN cruise MSM68 using Kongsberg EM 122 multibeam echosounder. The cruise took place between 06.10.2017 and 18.10.2017 off Svalbard. The cruise investigated the spreading processes at ultraslow spreading ridges. The aim was to understand how melts can travel to the widely spaced volcanic centers and force there their way upwards through lithosphere. Chief scientists: Schlindwein, Vera. An additional task was to acquire a high-resolution bathymetry map of the Knipovich Ridge [Doi: 10.2312/cr_msm68]. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry raw data ingest creation of products and approval. During the MSM68 cruise, the hull-mounted Kongsberg EM122 multibeam echosounder (MBES) was utilized to perform bathymetric mapping in middle to deep water depths. Two linear transducer arrays in a Mills Cross configuration transmit acoustic signals of a nominal sonar frequency of 12 kHz. With 432 soundings per swath, the emission cone has a dimension of max 150° across track and 2° along track. With a reception obtained from 288 beams, the actual beam footprint is 2° by 2°. Depending on the roughness of the seafloor, the swath width on a flat bottom is generally maximum six times the water depth. For further information on the system, consult https://www.km.kongsberg.com/. The angle was set to 65° during MSM68 [Doi: 10.2312/cr_msm68]. Responsible person during this cruise / PI: J. Geils & R. Brune. Postprocessing and products were conducted by the Seafloor-Imaging & Mapping group of MARUM/FB5, responsible person Paul Wintersteller (seafloor-imaging@marum.de). The open source software MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, https://www.mbari.org/products/research-software/mb-system, 2017) was utilized for this purpose. A sound velocity correction profile was applied to the MSM68 data; there were no further corrections for roll, pitch and heave applied during postprocessing. A tide correction was applied, based on the Oregon State University (OSU) tidal prediction software (OTPS) that is retrievable through MB-System. CTD measurements during the cruise were sufficient to represent the changes in the sound velocity throughout the study area. Using Mbeditviz, artefacts were cleaned manually. NetCDF (GMT) grids of the edited data as well as statistics were created with mbgrid. The published bathymetric EM122 grid of the cruise MSM68 has a resolution of 35 m. No total propagated uncertainty (TPU) has been calculated to gather vertical or horizontal accuracy. A higher resolution is, at least partly, achievable. The grid extended with _num represents a raster dataset with the statistical number of beams/depths taken into account to create the depth of the cell. The extended _sd -grid contains the standard deviation for each cell. The DTMs projections are given in Geographic coordinate system Lat/Lon; Geodetic Datum: WGS84.